Case its principles and its parameters - Baker, Mark C. (Cambridge studies in linguistics, 2015)
In Case, Mark Baker develops a unified theory of how the morphological case marking of noun phrases is determined by syntactic structure. Designed to work well for languages of all alignment types - accusative, ergative, tripartite, marked nominative, or marked absolutive - this theory has been developed and tested against unrelated languages of each type, and more than twenty non-Indo-European languages are considered in depth. While affirming that case can be assigned to noun phrases by function words under agreement, the theory also develops in detail a second mode of case assignment: so-called dependent case. Suitable for academic researchers and students, the book employs formal-generative concepts yet remains clear and accessible for a general linguistics readership